Self‐rescue of an EXTENSIN mutant reveals alternative gene expression programs and candidate proteins for new cell wall assembly in Arabidopsis. (16th May 2013) - Saha, Prasenjit; Ray, Tui; Tang, Yuhong; Dutta, Indrajit; Evangelous, Nicole R.; Kieliszewski, Marcia J.; Chen, Yuning; Cannon, Maura C.
Summary Plants encode a poorly understood superfamily of developmentally expressed cell wall hydroxyproline‐rich glycoproteins (HRGPs). One, EXTENSIN3 (EXT3) of the 168 putative HRGPs, is critical in the first steps of new wall assembly, demonstrated by broken and misplaced walls in its lethal homozygous mutant. Here we report the findings of phenotypic (not genotypic) revertants of the ext3 mutant and in‐depth analysis including microarray and qRT‐PCR (polymerase chain reaction). The aim was to identify EXT3 substitute(s), thus gaining a deeper understanding of new wall assembly. The data show differential expression in the ext3 mutant that included 61% (P ≤ 0.05) of the HRGP genes, and ability to self‐rescue by reprogramming expression. Independent revertants had reproducible expression networks, largely heritable over the four generations tested, with some genes displaying transgenerational drift towards wild‐type expression levels. Genes for nine candidate regulatory proteins as well as eight candidate HRGP building materials and/or facilitators of new wall assembly or maintenance, in the (near) absence of EXT3 expression, were identified. Seven of the HRGP fit the current model of EXT function. In conclusion, the data on phenotype comparisons and on differential expression of the genes‐of‐focus provide strong evidence that different combinations of HRGPs regulated by alternative gene expression networks, can make functioning cell walls, resulting in (apparently) normal plant growth and development. More broadly, this has implications for interpreting the cause of any mutant phenotype, assigning gene function, and genetically modifying plants for utilitarian purposes.